Potatoes Tanzania: Climate risk assessment - Groot, Annemarie; Duku, Confidence; Demissie, Teferi Dejene; Kabuka, Godfrey; Recha, John W.M. (CGIAR Research Program on Climate Change, Agriculture and Food Security, 2020)
Tanzania is the sixth largest producer of potatoes in Africa. They are generally grown in regions having an elevation of 1,800 and 2,700 meters above sea level. About 70 - 80% of the potatoes are produced in the Southern Highlands, particularly in the Iringa, Njombe and Mbeya regions. SAGCOT reported an annual potatoes production of over 1.7 million metric tons in the year 2017 (SGCOT, 2017). Average yield of potatoes ranges between 10 – 25 tons per hectare (Netherlands Enterprise Agency, 2017). Potato is also grown in Arusha, Eastern and in Kagera regions. In the Southern Highland, farmers grow two crops a year, in the short rainy season (Sept–Jan/Feb) and in the long rainy season (Feb-June/July). In the Eastern and Northern Zones, farmers grow one crop per year only (March - June/July). Potatoes are among the leading cash crops for smallholder farmers with about 88% of the potatoes grown sold for cash income (compared to 40 - 50% for beans, maize and rice). Potatoes are more profitable compared to cereals (especially in the highlands); with experts estimating three (3) fold higher incomes from potatoes (KilimoTrust, 2016). The area under potato production has increased exponentially over the years, as well as the production. Yields, however remain relatively low (Snyder et al., 2019), primarily due to low availability and use of quality seed, as well as limited knowledge of good agricultural practices. These – together with poor marketing structures, unstable prices, unspecified weights and measures, limited value addition and lack of crop promotion – restrict potato profitability among smallholder farmers.